Social Network Effects on Consumer Willingness to Pay for Biofortified Crops - Muange, Elijah N.; Oparinde, Adewale (My University, 2018)
Micronutrient deficiency, also known as hidden hunger, affects about two billion people globally. Adoption and consumption of micronutrient-enriched—that is, biofortified—staple crops, is a potential solution to alleviating hidden hunger. When creating demand for biofortified crops (seeds or food), social networks may complement “traditional” advertising channels, such as mass media. Ex-ante studies investigating the effects of nutrition information on acceptance of biofortified crops rarely assess explicitly the role of social networks. This study investigated the effects of social networks on consumer willingness to pay (WTP) for two highiron bean (HIB) varieties (HIB-A and HIB-B) using data collected from 572 farmers in rural Rwanda. The study used the Becker-DeGroot-Marshak mechanism to elicit consumer WTP in the absence and presence of radio messages providing positive and negative frames of information on nutritional benefits of HIB varieties at different frequencies. Instrumental variable and random effects models were used to assess the determinants of WTP. Results show that consumers were willing to pay more for the preferred HIB variety (HIB-A). The effect of social network size on demand could be positive or negative, depending on consumer perception of the product quality. Negative information about less preferred products can easily be spread within social networks, especially by men, who have larger networks than women, making it harder for media advertising alone to create sufficient demand for an inferior product. Media advertising positively influenced WTP only for the more preferred variety, but has a potential to increase WTP for the less preferred variety, if conducted more intensively and by using negative-framed information that emphasizes desirable product features
Keywords: Micronutrient; Biofortified